Fulfilling our educative mission: A response to edTPA critique - Whittaker, Andrea; Pecheone, Raymond L.; Stansbury, Kendyll (Education Policy Analysis Archives, 2018)
Stanford Center for Assessment, Learning, and Equity (SCALE) provides a commentary on the manuscripts in this special issue, responding to criticisms of edTPA as an assessment that narrows the curriculum, heavily relies on students’ academic writing skills, and creates additional burdens for teacher candidates. The commentary highlights how edTPA is intended to strengthen teacher candidates’ teaching and provides suggestions for educative implementation that could improve teacher education programs.